2013
DOI: 10.1074/jbc.m112.427062
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte ATP Production, Metabolic Flexibility, and Survival Require Calcium Flux through Cardiac Ryanodine Receptors in Vivo

Abstract: Background: Intracellular Ca 2ϩ release has been implicated in ATP production in vitro. Results: In vivo deletion of Ryr2 reduces Ca 2ϩ , ATP, and oxidative metabolism, leading to metabolic reprogramming and cell death. Conclusion: RYR2 maintains cardiomyocyte ATP production and survival in vivo.Significance: This work links heart metabolism to function via Ca 2ϩ release from intracellular stores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 58 publications
3
55
1
1
Order By: Relevance
“…Calpain 10 is present in cardiac mitochondria [36]. Activation of calpain 10 increases cell injury by impairing the mitochondrial respiratory chain [35] and is also involved in the disruption of ryanodine receptormediated apoptosis [36]. Therefore, activation of the mit-CPN1 and calpain 10 each appear to contribute to cell injury during ischemia-reperfusion.…”
Section: Localization Of Calpain Within Mitochondriamentioning
confidence: 98%
See 1 more Smart Citation
“…Calpain 10 is present in cardiac mitochondria [36]. Activation of calpain 10 increases cell injury by impairing the mitochondrial respiratory chain [35] and is also involved in the disruption of ryanodine receptormediated apoptosis [36]. Therefore, activation of the mit-CPN1 and calpain 10 each appear to contribute to cell injury during ischemia-reperfusion.…”
Section: Localization Of Calpain Within Mitochondriamentioning
confidence: 98%
“…In renal cortex mitochondria, calpain 10 is found in outer membrane, intermembrane space, inner membrane and matrix [35]. Calpain 10 is present in cardiac mitochondria [36]. Activation of calpain 10 increases cell injury by impairing the mitochondrial respiratory chain [35] and is also involved in the disruption of ryanodine receptormediated apoptosis [36].…”
Section: Localization Of Calpain Within Mitochondriamentioning
confidence: 99%
“…A recent paper has shown that VDAC2 is coupled to RyR2 in the heart (Min et al, 2012), allowing a direct coupling of RyR-mediated Ca 2+ release to Ca 2+ uptake in the mitochondria. Moreover, RyR-mediated Ca 2+ signaling has been implicated in ATP production and metabolic flexibility in the heart (Bround et al, 2013). Other studies have implicated RyRs in the regulation of apoptosis (Kim et al, 2002) and ER-stressmediated cell death (Luciani et al, 2009;Ruiz et al, 2009) in various cell types, including neurons and pancreatic b cells.…”
Section: K17dmentioning
confidence: 99%
“…Recent studies have shown that genetic variation in RNF207 is associated with prolongation of the QT interval [52,53] and that RNF207 knockdown in zebrafish embryos prolonged the action potential duration (APD) [21]. It was also reported that VDAC1 is the only identified protein mediating Ca 2+ transport in the outer mitochondrial membrane [54] and that Ca 2+ dynamics is important not only for APD [55,56] but also for the regulation of cellular energetic production [57][58][59]. These findings raised the possibility that RNF207 regulates cellular Ca 2+ dynamics, especially the mitochondrial Ca concentration.…”
Section: Discussionmentioning
confidence: 99%